Penerapan Metode Monte-Carlo untuk Analisis Toleransi Perubahan Nilai Komponen Terhadap Kinerja Osilator Frekuensi 2,3 GHz - Teguh Firmansyah; Gunawan Wibisono (Universitas Syiah Kuala, 2016)
In telecommunications equipment, an oscillator has a function to generate a carrier signal. As the carrier signal, a high stability performance is required. The frequency shift caused by component tolerances. In this research, a Monte-Carlo method was used to analyze a component tolerance on the performance of the oscillator at a frequency 2.3 GHz. A simulation was performed by software Advance Design System (ADS). In this research, the iterations were carried out as many as 212 times with tolerance component values by 10%. The analyzed performance consists of a fundamental frequency shift, a phase noise, the value of power fundamental, and a harmonic power. Meanwhile, the oscillator has a structure of bias BJT common base-bias BFR183 with Vcc = 20 V, Vce = 8.2 V and Ic = 15 mA and a dielectric resonator as a resonator. The oscillator has a fundamental frequency 2.3 GHz, phase noise -135.6 dBc / Hz, power fundamental 10.8 dBm, and harmonic power -11.2 dBm. The simulation results showed that the oscillator has a good performance with a high degree of stability on a fundamental frequency by 73%, stability phase noise 100%, stability power fundamental 64%, and stability harmonic power 61%. This simulation has a confidence level of 95.4%, an error ± 3%, and the estimation accuracy 95%.